BindingDB Entry 50046925: Synthesis, experimental evaluation and molecular modelling of hydroxamate derivatives as zinc metalloproteinase inhibitors. - BindingDB (BindingDB, 2017)
Small molecule binding data for protein ADAM17, Collagenase, Pseudolysin, and Thermolysin, Uniprot P00800, P08253, P14756, P14780, and P78536